Water Resources Conservation in Bali: A Non-cooperative Game Theory Approach - I Wayan Sukadana; I Komang Gde Bendesa; Ni Putu Wiwin Setyari; I Gusti Wayan Murjana Yasa (Jurnal Ekonomi Pembangunan, 2023)
Entering the 21st century, the world faces a global water crisis threat, due to increasing competition for freshwater which is an implication of economic growth, population growth, and climate change. Therefore, institutions that can secure the availability of water resources sustainably are urgently needed. In contrast to the tendency of research in the last two decades, which was dominated by experimental methods, this research studies local institutions in Bali called Subak using game theory as a reasoning method. Water management was analyzed using three economic frameworks namely, institutions, transaction costs, and contracts, to reveal how water institutions in Bali are managed. This study found that there are strong social norms that can maintain trust, act as a coordinating medium, eliminate transaction costs, and enforce contracts. Furthermore, the study also discusses the failure possibility of the current government intervention system because the capitalist production function alienates the value of water from its production system. Empirical research through experiments is very important, however, economics has a set of theories that can be used to predict or develop incentive mechanisms within an institution. The social norms that were found in this study can be used as a basis for the design of clean water management institutions at the village or community level with public participation.